Elaboración de un antígeno para parásitos gastrointestinales (Cooperia Spp) en Ovinos - Quinatoa Castellano, Steeven Joel (2023)
This research aims to develop a parasite antigen of Cooperia spp in sheep to induce an immune response and improve production in a flock located in the rural community of Cuasualó belonging to the Zumbahua parish. From a sample of 50 sheep using the flotation technique, 30 individuals presented Cooperia spp eggs at an estimated age of 0-3 years, of which 22 were females and 8 males. According to the results obtained in the Chi-square test with a critical value of 3.84 and a calculated value of 0.07, Evidencing that there is no relationship between the sex of the animal and the parasite load; according to the results of the Pearson's correlation coefficient, a value of -0.164 and a determination of 0.027 were obtained, therefore a weak negative correlation was established, considering that as the age of a sheep increases, the parasite load tends to decrease. The morphological identification through the use of lactophenol allowed to categorize the adult parasites with the typical characteristics of Cooperia spp showing a reddish-whitish coloration, its head swelled by a prominent cephalic vesicle, its longitudinal edges with transverse striations, short spicules with a rounded tip. and the cuticle in the stomach region was transversely striated and slightly domed. The parasite maceration technique allowed the elaboration of the Cooperia spp antigen by centrifuging the sample and absorbing the supernatant containing the parasite proteins and allowing the typing of the antigen by applying the Kjeldahl method as a subunit vaccine with 1.43% protein. , which was inoculated in each of the sick animals within the herd. The use of sheep represents the livelihood of a family, so it was sought to change the traditional control mechanism that is currently undergoing resistance to antiparasitics. Vaccines are a new alternative in the control and prevention of one of the infestations that most affect sheep and the economy of farmers. This strategy generates a social impact and a benefit in the human-animal-environment triad, where the product developed, being a protein, does not cause damage to the environment, integrating the 3 elements and developing a more sustainable production.